Temozolomide chemotherapy for progressive low-grade glioma: clinical benefits and radiological response - Pace, A.; Vidiri, A.; Galiè, E.; Carosi, M.; Telera, S.; Cianciulli, A. M.; Canalini, P.; Giannarelli, D.; Jandolo, B.; Carapella, C. M. (Annals of oncology, 2003)
Background: The optimal treatment for low-grade glioma (LGG) is still controversial. Recent data indicate a potential influence of chemotherapy on the natural evolution of these tumors, allowing for the deferral of more aggressive therapies. Patients and methods: Forty-three patients affected with LGG (29 astrocytoma, four oligodendroglioma and 10 mixed oligo-astrocytoma) were treated with temozolomide (TMZ) at the time of documented clinical and radiological progression. McDonald’s response criteria were utilized to evaluate TMZ activity. Thirty patients (69.7%) had previously received radiotherapy; 16 (37.2%) had received prior chemotherapy. Clinical benefit was evaluated measuring seizure control, reduction in steroid dose and modification of Karnofsky performance status and Barthel index. Quality of life was assessed with the QLQ-C30 questionnaire. Results: We observed a complete response in four patients, 16 partial responses, 17 stable disease (with four minor response) and six progressive disease. Median duration of response was 10 months [95% confidence interval (CI) 8–12], with a 76% rate of progression free survival (PFS) at 6 months, and a 39% rate of PFS at 12 months. A relevant clinical benefit was observed particularly in patients presenting epilepsy. Conclusions: The high response rate of 47% (95% CI 31% to 61%) confirms that TMZ chemotherapy is a valid option in the treatment of progressive LGG. The present preliminary results seem interesting and warrant further evaluation of TMZ clinical activity in a larger series of progressive LGG.